1999
DOI: 10.1128/jb.181.10.3144-3154.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Streptococcal Competence ( com ) Gene Locus

Abstract: The com operon of naturally transformable streptococcal species contains three genes, comC, comD, andcomE, involved in the regulation of competence. ThecomC gene encodes a competence-stimulating peptide (CSP) thought to induce competence in the bacterial population at a critical extracellular concentration. The comD and comEgenes are believed to encode the transmembrane histidine kinase and response regulator proteins, respectively, of a two-component regulator, with the comD-encoded protein being a receptor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 29 publications
3
64
1
Order By: Relevance
“…Therefore, the loss of the three amino acids (-LGK) at the carboxyl end of the peptide (CSP-2 & CSP-3) or substitution of tyrosine for serine at position 3 of the mature CSP (CSP-3) does not impair the function of these peptides. Furthermore, in contrast to the pherotype specificity reported in S. pneumoniae (Pozzi et al, 1996;Whatmore et al, 1999), representative strains encoding either CSP-1 or CSP-2 showed increased transformation in response to all three mature synthetic CSPs. Therefore, distinct strains of S. mutans can readily cooperate in genetic exchange.…”
Section: Transformation Phenotype Of Selected Strains To Synthetic Cspscontrasting
confidence: 84%
“…Therefore, the loss of the three amino acids (-LGK) at the carboxyl end of the peptide (CSP-2 & CSP-3) or substitution of tyrosine for serine at position 3 of the mature CSP (CSP-3) does not impair the function of these peptides. Furthermore, in contrast to the pherotype specificity reported in S. pneumoniae (Pozzi et al, 1996;Whatmore et al, 1999), representative strains encoding either CSP-1 or CSP-2 showed increased transformation in response to all three mature synthetic CSPs. Therefore, distinct strains of S. mutans can readily cooperate in genetic exchange.…”
Section: Transformation Phenotype Of Selected Strains To Synthetic Cspscontrasting
confidence: 84%
“…Sequence comparison of the deduced peptide in a total of 10 strains revealed another 28-residue variant (Table 1). Thus, the signaling molecule and the sensor domain of the receptor kinase occur as distinct functional units, similar to the allelic variants described for the comC/comD pair where activation of the receptor kinase requires the presence of the matching peptide ( [17,18] and references therein).…”
Section: Resultsmentioning
confidence: 85%
“…Following the initial identification of the comC gene in strain CP1200 (Håvarstein et al, 1995a), this gene has been sequenced in a large number of strains from species such as S. pneumoniae, Streptococcus mitis, Streptococcus oralis and other members of the mitis phylogenetic group (Pozzi et al, 1996;Håvarstein et al, 1997;Ramirez et al, 1997;Whatmore et al, 1999;Johnsborg et al, 2007a). This work has revealed that there exists extensive diversity with respect to the primary amino acid sequences of CSPs produced by various strains and species.…”
Section: Extracellular Csp Is Sensed By a Two-component Regulatory Symentioning
confidence: 99%